Constructing an optimal facility layout to maximize adjacency as a function of common boundary length. Issue 3 (4th March 2018) - Ghassemi Tari, Farhad; Neghabi, Hossein
ABSTRACT: An effective facility layout implies that departments with high flow are laid adjacent. However, in the case of a very narrow boundary length between the neighbouring departments, the adjacency would actually be useless. In traditional layout design methods, a score is generally assigned independent of the department's boundary length. This may result in a layout design with a restricted material flow. This article proposes a new concept of adjacency in which the department pairs are laid adjacent with a wider path. To apply this concept, a shop with unequal rectangular departments is contemplated and a mathematical programming model with the objective of maximizing the sum of the adjacency degrees is proposed. A computational experiment is conducted to demonstrate the efficiency of the layout design. It is demonstrated that the new concept provides a more efficient and a more realistic layout design.